Acanthamoeba keratitis: A 4-year review from a tertiary care hospital in North India - Megha, Kirti; Thakur, Anchal; Khurana, Sumeeta; Sehgal, Rakesh; Gupta, Amit (Nepalese Journal of Ophthalmology, 2020)
Introduction: Acanthamoeba keratitis (AK) is a blinding condition reported from both developed and developing countries. Limited knowledge on the clinical characteristics of AK and scarce laboratory diagnostic facilities in such countries poses difficulties in the accurate diagnosis.Objective: To describe the epidemiological and clinical characteristics as well as management of Acanthamoeba keratitis in a tertiary care hospital in North India.Methods: All clinically suspicious cases of Acanthamoeba keratitis (AK) presenting to our centre were screened for Acanthamoeba. All patients diagnosed as Acanthamoeba on microscopic examination, culture and polymerase chain reaction (PCR) were given Polyhexamethylene biguanide (PHMB) eye drops 0.02% half hourly for 1 week, then hourly for 1 week and then gradually tapered according to the response. Out of 300 consecutive patients evaluated, Acanthamoeba was detected in 11(3.6%) patients. A history of trauma was elicited in majority of the patients, 6 (55%). The most common complaints were eye pain, redness and watering in all of the patients, diminution of vision (8, 72.7%), photophobia (7, 63.6%) and foreign body sensation (2, 18.2%). Complete healing with vascularization and scarring was observed in 7 patients (63.6%) patients whereas progression to perforation of corneal ulcer and corneal melt was seen in 3 (27.3%) cases and these patients underwent therapeutic keratoplasty later. One patient did not come for follow up examination.Conclusion: The most common risk factor for the occurrence of Acanthamoeba Keratitis is trauma followed by contact lens use.